Major mechanisms maintaining the regulation of hemostasis - Ramazan Çöl; Zafer Durgun (Eurasian Journal of Veterinary Sciences)
Hemostasis may be defined as the process that prevents blood loos from sites of vascular disruption. Normal hemostasis is maintained by a delicate balance between the procoagulant and anticoagulant mechanism, distruplion of this balance can lead to either excessive bleeding or to clot formation. This review presents information about a series complex mechanisms divided into two groups as primer and secondary hemostasis.